Research on ICT in Teacher Education in Chile: A Systematic Review - Tapia Silva, Hugo (2025)
Introduction: In the Chilean context, integrating Information and Communication Technologies (ICT) into Initial Teacher Education (ITE) is a key challenge for modernizing education. Despite efforts to incorporate ICT standards, significant gaps persist, including gender disparities and the practical application of digital competencies. Background: A systematic review was conducted following PRISMA guidelines. The search was performed in Web of Science, Scopus, and Scielo, applying inclusion criteria such as peer-reviewed articles, open access, and publications from 2013 onward. A total of 31 articles were selected, addressing digital competencies, curriculum design, and technological innovations in ITE. The analyzed studies highlighted three main areas: digital competencies, ICT-integrated curricula, and pedagogical innovations. Discussion: Discrepancies were identified between self-perceived and actual performance of digital competencies, alongside gender gaps. Regarding curriculum integration, specific ICT-focused courses are more prevalent than transversal approaches. The findings underscore the need to advance toward practical assessments that evaluate real-world performance in pedagogical contexts. Additionally, inclusive strategies are essential to address gender gaps and foster innovative pedagogical models, such as flipped classrooms and immersive technologies.